Genetic variation in cis-regulatory domains suggests cell type-specific regulatory mechanisms in immunity - Avalos, Diana; Rey, Guillaume; Ribeiro, Diogo M.; Ramisch, Anna; Dermitzakis, Emmanouil T.; Delaneau, Olivier (Communications biology, 2023)
Studying the interplay between genetic variation, epigenetic changes, and regulation of gene expression is crucial to understand the modification of cellular states in various conditions, including immune diseases. In this study, we characterize the cell-specificity in three key cells of the human immune system by building cis maps of regulatory regions with coordinated activity (CRDs) from ChIP-seq peaks and methylation data. We find that only 33% of CRD-gene associations are shared between cell types, revealing how similarly located regulatory regions provide cell-specific modulation of gene activity. We emphasize important biological mechanisms, as most of our associations are enriched in cell-specific transcription factor binding sites, blood-traits, and immune disease-associated loci. Notably, we show that CRD-QTLs aid in interpreting GWAS findings and help prioritize variants for testing functional hypotheses within human complex diseases. Additionally, we map trans CRD regulatory associations, and among 207 trans-eQTLs discovered, 46 overlap with the QTLGen Consortium meta-analysis in whole blood, showing that mapping functional regulatory units using population genomics allows discovering important mechanisms in the regulation of gene expression in immune cells. Finally, we constitute a comprehensive resource describing multi-omics changes to gain a greater understanding of cell-type specific regulatory mechanisms of immunity. An analysis of cis-regulatory domains (CRDs) among monocytes, neutrophils, and T cells derived from ChIP-seq peaks and methylation data suggests cell-type specific regulatory mechanisms of immunity.